Catcalling Sebagai Prediktor Self Esteem Pada Perempuan Muda: ‎Implikasinya untuk Layanan Bimbingan dan Konseling - Fitri, Kartika Ayu; AR, Silvia (Program Studi Bimbingan dan Konseling FKIP UMSU, 2025)
The purpose of this study was to see the effect of catcalling treatment on self esteem in female students. Catcalling is a form of verbal sexual harassment that is common in public spaces and can have an impact on the psychological aspects of victims, especially self esteem. This study used a quantitative approach with a correlational method. The study population consisted of female students in six universities in Palembang City, with a sample of 404 respondents obtained through purposive sampling technique. The results of data analysis using simple linear regression showed a negative and significant influence between catcalling treatment on self esteem in female students (p 0.05). That is, the higher the intensity of catcalling treatment experienced, the lower the level of self esteem owned by female students. The implications of this research can be applied in guidance and counseling services to help victims of catcalling in increasing self esteem.